A low cost technique to evaluate usable product for small manufacturing companies: a case study on Garcia robot. - Soares, Marcelo M.; Jacobs, Karen; An, Vatana; Soares, Marcelo (Work)
A usability evaluation technique to evaluate user interfaces is introduces. The technique is effective and affordable for small manufacturing companies. By using this technique, an integration of users' feedbacks and some usability concepts, a product can be 3 times easier to use among potential users and more than 5 times easier to use among motivated users. In addition, the technique can be implemented with the company's employees as participants.